Closed equations for the design of class f amplifiers - Moreno-Rubio, Jorge Julián; Rodríguez-Mora, Javier Francisco; Cely-Angarita, Nydia Esperanza; Angarita-Malaver, Edison Ferney (Universidad Pedagógica y Tecnológica de Colombia, 2015)
This paper shows a methodology for designing class F amplifiers based on closed equations that allow the direct calculation of the output matching network. For the sake of proving, a prototype has been carried out using the Cree´s device GaN HEMT CGH40010, obtaining a maximum drain efficiency of 65 %, small signal gain of 14.2 dB and saturated output power of 41 dBm, using sinusoidal excitation. The drain voltage and current waveforms are coherent with theory and the results in continuous-wave are outstanding.